2019
DOI: 10.3390/soilsystems3040065
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Prediction of Soil Texture Fractions in Arid Regions of Iran

Abstract: To predict the soil texture fractions, 115 profiles were identified based on the Latin hypercube sampling technique, the horizons were sampled, and the clay, sand, and silt contents (in percentages) of soil samples were measured. Then equal-area quadratic spline depth functions were used to derive clay, sand, and silt contents at five standard soil depths (0–5, 5–15, 15–30, 30–60, and 60–100 cm). Auxiliary variables used in this study include the terrain attributes (derived from a digital elevation model), Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…MrVBF was an effective index in the flat areas, especially for identifying flat valley bottoms which can be used effectively for the prediction of soil texture classes (Taghizadeh-Mehrjardi et al, 2014). MrVBF was identified as the most important variable along with spectrometric data for the prediction of soil texture fraction in the arid region of Iran (Mehrabi-Gohari et al, 2019). Similarly, Jafari et al (2014) predicted soil texture classes using boosted RT in an arid region and found MrVBF and moisture indices are important auxiliary variables for their model.…”
Section: Importance Of Variablesmentioning
confidence: 90%
See 1 more Smart Citation
“…MrVBF was an effective index in the flat areas, especially for identifying flat valley bottoms which can be used effectively for the prediction of soil texture classes (Taghizadeh-Mehrjardi et al, 2014). MrVBF was identified as the most important variable along with spectrometric data for the prediction of soil texture fraction in the arid region of Iran (Mehrabi-Gohari et al, 2019). Similarly, Jafari et al (2014) predicted soil texture classes using boosted RT in an arid region and found MrVBF and moisture indices are important auxiliary variables for their model.…”
Section: Importance Of Variablesmentioning
confidence: 90%
“…Though several studies exist for mapping of soil particle size for different depth intervals using regression algorithms (Akpa et al, 2014;Hengl et al, 2017;Mehrabi-Gohari et al, 2019;Pahlavan-Rad & Akbarimoghaddam, 2018;Poggio & Gimona., 2017;Taghizadeh-Mehrjardi et al, 2020;Taghizadeh-Mehrjardi et al, 2016), mapping of categorical variables such as soil texture classes at different depth intervals is not well documented. In this context, the present study is aimed to apply equal-area quadratic spline function over average sand, silt and clay content of different texture classes for deriving texture classes for six standard depth intervals.…”
Section: Introductionmentioning
confidence: 99%
“…The use of ML models has become increasingly prevalent for predicting the spatial distribution of soil properties. When predicting soil PSFs, various ML-based DSM studies have included the use of artificial neural networks (ANNs) [17][18][19][20][21], boosted regression tree (BRT) [19,22,23], Random Forest (RF) [18,24], and artificial neuro-fuzzy inference system (ANFIS) [16,25]. Despite the variety of ML models that a DSM practitioner may apply, existing literature does not seem to suggest that one model is universally better than others; furthermore, model comparison studies have shown that different models have the potential to generate drastically different outputs when given the same input data [26].…”
Section: Introductionmentioning
confidence: 99%
“…Again, in the random forest modelling process of the silt fraction, the most important variable at the IncNodePurity significance level, which represents the reduction of node impurity in the formation of trees, was the F I G U R E 6 Importance in levels of the environmental variables used to predict the content of soil texture fractions using the random forest algorithms, (a, d) clay, (b, e) sand, and (c, f) silt topographic wetness but with a higher difference from GNDVI (Figure 6). The topographic wetness index, which is an important topography variable that affects the amount of moisture accumulation in the soil (Mehrabi-Gohari et al, 2019), can be considered as an important variable in modelling the silt fraction. In terms of showing areas with high moisture accumulation potential, its effect on the estimation of silt content has been reported in other studies (Moore et al, 1993;Nabiollahi et al, 2014;Pinheiro et al, 2018).…”
Section: Importance Of the Environmental Covariatesmentioning
confidence: 99%